Strategi Pembelajaran di Pondok Pesantren Ma’hadut Tholabah Babakan Lebaksiu Tegal Pada Era Pandemi Covid-19 - Ikhda Nurnoviyati (Jurnal Ilmiah Wahana Pendidikan, 2022)
Islamic Boarding School is an educational institution located in the Indonesian community with a coaching model that is full of value education, both religious values ​​and the noble values ​​of the nation. Ma'hadut Tholabah Babakan Islamic Boarding School is a salaf Islamic boarding school (salafiyah) located in Tegal Regency and integrated with formal school education. Ma'hadut Tholabah Babakan Islamic Boarding School is one of the educational institutions that instills religious values, nationalism, religious character, educational context and prevents negative things that occur along with the times. learning methods in the pesantren environment apply the "ta'lim" (teaching) system. Methodically, education and teaching in Islamic boarding schools are given in the form of: sorogan, bandongan, halaqah, and memorization. However, due to Covid-19, this teaching method cannot be fully implemented with inherent habits. Therefore, the Board of Directors of the Ma'hadut Tholabah Babakan Islamic Boarding School one of the learning strategies by including one A'dlo Council (Management) / Coordinator in each room to guide and direct other students in the room to maintain health and monitor if there are any. students who are affected by the symptoms of the corona virus, besides the kyai also carry out learning with strict procedures, one of which is by wearing masks when learning at Islamic boarding schools. This is expected to fulfill the right to education for its students even though the results are not optimal.